Legal Consequences of Nominee Made Before a Notary Based on Legal Certainty in the Perspective of the Conditions for the Validity of the Agreement - Husen, Arie Arisandy; Riyanto, Taufan Fajar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Currently, many people use the nominee (borrow name) agreement. Some of the reasons include those who have been blacklisted from the bank because of the inability to pay their installments, there are those whose BI Checking has entered collect 5 but wants to make loans to banks such as mortgages or car loans. In practice, there are notaries who dare to make nominee agreements to help clients who have problems in banking or foreigners who want to own land in Indonesia. Even though the UUPM and UUPA are prohibited from using the borrowed name. The purpose of this study is to find out and analyze the legal consequences and validity of the nominee agreement made before a notary. The approach method used in this study is a normative juridical approach, namely by examining reading sources that are relevant to the research theme, including research on legal principles, legal sources, statutory regulations that are scientific theoretical in nature and can analyze the issues discussed. The results of his research are the validity of a nominee agreement (borrow name) that occurs in Indonesia, when viewed from the Civil Code in Article 1320 regarding the legal requirements of an agreement, precisely on the objective conditions, namely paragraph 4 does not fulfill the legal requirements of an agreement. So that a Name Borrow Agreement that occurs in Indonesia, if viewed from the applicable law, it can be seen that the agreement is said to be null and void. A notary may be subject to sanctions in the form of civil, administrative and ethical sanctions, as well as criminal sanctions for the legal consequences arising from the nominee agreement deed he made, as long as the elements for imposing sanctions are fulfilled. Notaries may be subject to sanctions in the form of civil, administrative and code of ethics sanctions. Keywords: Agreement; Consequences; Nominee; Validity.